Determinación de valores de referencia de ácido úrico sérico en personas aparentemente sanas que acuden al Banco de Sangre del Hospital Sub Regional de Andahuaylas. Mayo - julio del 2018 - Ortiz Guizado, Edwin Eluid (2019)
The reference values, important data in the diagnosis support, must be elaborated by the same laboratory, that is why the present work was carried out, in a population, of 191 apparently healthy people (85 women and 106 men), all of them They went to the Blood Bank of the Sub-Regional Hospital of Andahuaylas, during the months of May, June and July of 2018. eference values for serum uric acid were obtained, in men 2.38 to 7.62 mg / dl, and women from 2.16 to 6.59 mg / dl, of course, that these differ from those offered by the bibliography. The concentrations of this analyte in women are always lower than that of men, as shown in the present study; On the other hand it could be shown that there is no relationship between the concentration of hematocrit and uric acid values, as there are individuals with a higher level hematocrit (53%), who may have low uric acid values and, conversely, values at the upper limit of uric acid and hematocrit at the lower level (42%). The diet is very important for the production of exogenous uric acid, it follows that when the intake of foods rich in purines is higher, the values are higher, thus it was possible to verify that people who in their weekly diet ingest more Sometimes red meats have high concentrations of uric acid in serum.